A case of simultaneously detected rectovaginal fistula and atresia ani in a kitten (VETERINARIA, 2023)
A 45-day-old female kitten was admitted to the Obstetrics and Gynaecology Clinics of Faculty of Veterinary Medicine at Istanbul University-Cerrahpaşa with complaints of vomiting, abdominal swelling and difficulty in defecation after switching to dry food. The mucous membranes were pale pink, the palpable lymph nodes were of normal size, the furs were dull, the abdomen was swollen, intestinal fullness, and the normal posture on all fours were noticed. On clinical examination, it was seen that the anus was completely closed, and the faeces was coming from the vagina. In this case, Type II atresia and recto-vaginal fistula were observed simultaneously. General anesthesia was administered to the kitten whose vital signs and hemogram values were within the normal reference range, and an anal opening surgery was performed. In this case report, the surgical intervention of the rarely seen congenital defects andthe post-surgery process were discussed. It is concluded that the atresia ani and recto-vaginal fistula cases, which are successfully treated by a surgical intervention, may simultaneously exist in 45-day-old kittens, and both clinical and surgical approaches at an early age would have great importance in such congenital cases.
Keywords: cat; congenital defect; surgical therapy